Effect of Virtual Reality Therapy with Brain Gym Exercises for Sleep-deprived Individuals: A Randomized Clinical Trial - Marissa De Souza Eremita; Jeba Chitra (Archives of Medicine and Health Sciences)
Background and Aim: Sleep deprivation refers to getting less than the required amount of sleep, which for adults range between 7 and 9 h per night and can be caused due to social and biological factors. Virtual reality therapy (VRT) allows individuals to experience a computer-generated virtual environment so that they can be exposed to stimuli that imitate real-world experiences and have been used in other psychological conditions with positive outcomes. Brain Gym (BG) is a kinesiology program that engages the participant in a number of activities that teach the body how to comprehend the primary behavior and coordinate the brain and body. Materials and Methods: A randomized clinical trial was performed by screening 51 samples, from which 32 individuals were recruited, using purposive sampling, based on the Pittsburgh Sleep Quality Index (PSQI) which was used as the inclusion criteria. VRT session was for 15 min and BG exercises were given thrice a week for 4 weeks. The PSQI and Athens Insomnia Scale (AIS) were used as the outcome measures and were assessed after the intervention. The Shapiro–Wilk test, paired t-test, and independent sample t-test were used for the statistical analysis of the data. Results: There was a significant difference between the pre- and postscores of the PSQI of Group A (Pre – 7.00 ± 1.55; Post – 6.31 ± 2.06; P = 0.029) and Group B (Pre – 8.44 ± 2.63; Post – 6.19 ± 2.97; P = 0.001), although Group B showed a better improvement, based on the effect size (1.06) and Group B (Pre – 7.13 ± 2.58; Post – 5.63 ± 2.60) showed a significant difference in the pre- and postvalues of the AIS (P = 0.011). Conclusion: The study concluded that VRT and BG exercises were effective interventions, although BG exercises were shown to be more effective than the virtual reality intervention.